2023
DOI: 10.1080/02699931.2023.2222579
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in emotion recognition: investigating the moderating effects of stimulus features

Abstract: The manuscript will undergo copyediting, typesetting, and review of resulting proof before it is published in its final form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It has been found that male participants showed a larger happy face facilitation effect of male faces compared to female faces in expression recognition ( 54 ). Female participants were found to have an advantage in the recognition of negative emotions, such as fear and anger ( 55 ). Moreover, sex differences in facial expression perception were also influenced by other factors ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that male participants showed a larger happy face facilitation effect of male faces compared to female faces in expression recognition ( 54 ). Female participants were found to have an advantage in the recognition of negative emotions, such as fear and anger ( 55 ). Moreover, sex differences in facial expression perception were also influenced by other factors ( 56 ).…”
Section: Discussionmentioning
confidence: 99%